Involvement of HCN Channel in Muscarinic Inhibitory Action on Tonic Firing of Dorsolateral Striatal Cholinergic Interneurons - Zhao, Zhe; Zhang, Kang; Liu, Xiaoyan; Yan, Haitao; Ma, Xiaoyun; Zhang, Shuzhuo; Zheng, Jianquan; Wang, Liyun; Wei, Xiaoli (Frontiers in Cellular Neuroscience, 2016)
The striatum is the most prominent nucleus in the basal ganglia and plays an important role in motor movement regulation. The cholinergic interneurons (ChIs) in striatum are involved in the motion regulation by releasing acetylcholine (ACh) and modulating the output of striatal projection neurons. Here we report that muscarinic acetylcholine receptor (M receptor) agonists, ACh and Oxotremorine (OXO-M), decreased the firing frequency of ChIs by blocking the hyperpolarization-activated cyclic nucleotide-gated (HCN) channels. Scopolamine (SCO), a nonselective antagonist of M receptors, abolished the inhibition. OXO-M exerted its function by activating the Gi/o cAMP signaling cascade. The single-cell reverse transcription polymerase chain reaction (scRT-PCR) revealed that all the five subtypes of M receptors and four subtypes of HCN channels were expressed on ChIs. Among them, M2 receptors and HCN2 channels were the most dominant ones and expressed in every single studied cholinergic interneuron (ChI). Our results suggest that ACh regulates not only the output of striatal projection neurons, but also the firing activity of ChIs themselves by activating presynaptic M receptors in the dorsal striatum. The activation of M2 receptors and blockage of HCN2 channels may play an important role in ACh inhibition on the excitability of ChIs. This finding adds a new G-protein coupled receptor mediated regulation on ChIs and provides a cellular mechanism for control of cholinergic activity and ACh release in the dorsal striatum.